(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The Progress in International Reading Literacy Study (PIRLS) is a periodic monitoring study of the quality and trends of reading literacy in countries with different education systems. Allows you to compare the level and quality of reading and understanding of written text by primary school students around the world, as well as identify and compare changes taking place in national education systems.